Electronic properties of fluorides by efficient approximated quasiparticle DFT-1/2 and PSIC methods: BaF2, CaF2 and CdF2 as test cases. (13th August 2018) - Matusalem, Filipe; Marques, Marcelo; Teles, Lara K; Filippetti, Alessio; Cappellini, Giancarlo
Abstract: Dialkali halides are materials of great interest from both fundamental and technological viewpoints, due to their wide transparency range. The accurate determination of their electronic, excitation and optical properties in bulk and low dimensional systems is therefore of crucial importance. Moreover, it is a challenge from the theoretical point of view to deal with quasiparticle band structure calculations for such large energy gap materials, requiring very expensive methods for achieving a desirable accuracy. Here we report electronic quasiparticle band structures for three representative bulk fluorides, BaF2, CaF2 and CdF2, calculated using two low computational cost methods, the DFT-1/2 and the PSIC schemes, which have been relatively little explored by the theoretical community so far. Our results, compared with both available experimental data and previous heavyweight DFT-GW self-energy calculations, demonstrate a satisfactory accuracy for the examined compounds, at a level comparable with the perturbative G0 W0 approach. Remarkably, both our proposed methods scale quite similarly to standard local density functional approaches, thus resulting in a large saving of computational effort with respect to the computationally heavyweight GW. Our results open up the perspective of the computational exploration of much bigger fluoride systems. As a significant proof of concept of this capability, we also calculated the quasiparticle properties of the (1 1 1) surfaces of all the three systems under study. Very good agreement with experiment was found.